Risk factors of status epilepticus in children - A literature review - Mularczyk, Klaudia; Znamirowska, Patrycja; Paszkowska, Monika; Karaban, Łukasz; Kupis, Magdalena; Jakubiak, Anna; Miśkiewicz, Joanna; Borawski, Michał; Ciuła, Aleksandra; Kuźnieców, Tadeusz (Quality in Sport, 2025)
Introduction: Status epilepticus is one of the most common and severe neurological emergencies in children. It is defined by prolonged or recurrent seizures without full recovery in between and is associated with significant morbidity and mortality. This study aims to identify predictors of SE development and poor prognosis in children. Material and Methods: A focused literature search was conducted in PubMed for studies published between 2015 and 2025, targeting human research related to pediatric status epilepticus. Search terms included “status epilepticus”, “children” and “risk factors”. Relevant meta-analyses, observational studies, and clinical trials were reviewed and evaluated for methodological quality and clinical significance. State of Knowledge: SE is a neurological emergency, where ongoing seizures lead to drug resistance and brain injury. Classification by seizure duration informs treatment urgency. Benzodiazepines, especially intramuscular midazolam, remain first-line, with levetiracetam as a common second-line option. While mortality is declining, outcomes depend on seizure length, cause, and care setting, underscoring the need for rapid intervention. Discussion: This study identifies key clinical and laboratory factors influencing the development and outcomes of SE in children. Younger age, perinatal complications, neurodevelopmental delays, and prolonged or biphasic seizures were significantly linked to higher risk and poorer outcomes. Laboratory markers were also associated with worse prognosis. Infectious, autoimmune, and genetic etiologies emerged as important underlying causes of SE, underscoring the need for early identification and targeted interventions. Conclusion: Early age, early-life complications, seizure duration, and metabolic imbalances are major indicators of poor prognosis in pediatric status epilepticus. Recognizing infectious, autoimmune, and genetic triggers is essential for timely and effective intervention.